Spaceborne radiance temperature standard blackbody for Chinese high-precision infrared spectrometer. (27th October 2020) - Hao, Xiaopeng; Song, Jian; Ding, Lei; Wen, Ping; Sun, Jianping; Liu, Yang; Yuan, Zundong; Duan, Yuning; Zhang, Yong
Abstract: As a radiance temperature standard source for the Chinese high-resolution spectrum infrared spectrometer, the National Institute of Metrology, China, developed a spaceborne radiance temperature standard blackbody (SRTSB) combined with a series of miniature phase change fixed points (MPCFPs) for temperature calibration and emissivity verification using a thermal radiation loop (TRL). The MPCFPs of the SRTSB contain H2 O, Ga, Ga–Sn alloy, and phenyl salicylate. The TRL is used to measure the emissivity of the spaceborne blackbody on the basis of controlling environmental radiation. Experimental results show that the blackbody emissivity is higher than 0.998 and the temperature control stability is better than 5 mK. Temperature control uniformity at the cavity bottom and axial are better than or equal to 11 mK and 38 mK, respectively, in the working temperature range of 268.15 K to 331.15 K.. The repeatability of the MPCFPs is less than 5 mK, and the results of the continuous phase transition of the MPCFPs are in a clear temperature plateau. The expanded uncertainty of the SRTSB is lower than or equal to 0.084 K ( k = 2).